1990
DOI: 10.1039/an9901500933
|View full text |Cite
|
Sign up to set email alerts
|

Determination of non-metallic elements by capacitively coupled helium microwave plasma atomic emission spectrometry with capillary gas chromatography

Abstract: A capacitively coupled microwave helium plasma with a tubular tantalum electrode was evaluated as an element selective detector for gas chromatography (GC). The end of a 10-m bonded fused capillary column was directly inserted into the tubular electrode without any switching system. A heated copper tube was used to house the part of the GC column that protruded from the oven. The optimisation of operating parameters, line selection, background emission and horizontal and vertical observation position is descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Relevant studies for comparison are scarce in the literature, but the response variations observed in the present work were in accordance with similar studies on organic compounds performed with gas chromatographic introduction to different plasma systems. 37,[39][40][41][42] The excellent response of Rhodamine B supported the fact that the method is applicable also for chlorinated compounds not amenable to gas chromatography. Unfortunately, highly volatile compounds like dichloro-and dibromobenzene were not detected with the dual-plasma system.…”
Section: Resultsmentioning
confidence: 90%
“…Relevant studies for comparison are scarce in the literature, but the response variations observed in the present work were in accordance with similar studies on organic compounds performed with gas chromatographic introduction to different plasma systems. 37,[39][40][41][42] The excellent response of Rhodamine B supported the fact that the method is applicable also for chlorinated compounds not amenable to gas chromatography. Unfortunately, highly volatile compounds like dichloro-and dibromobenzene were not detected with the dual-plasma system.…”
Section: Resultsmentioning
confidence: 90%
“…In the course of developing element-specific detectors for gas chromatography, many helium plasmas have been proposed for the detection of nonmetals in chromatographic eluents by optical emission spectrometry (OES) or mass spectrometry (MS). Although, so far, the atmospheric pressure microwave-induced plasma (MIP)-OES could be considered the most popular technique for this particular purpose, many other different combinations, using both atmospheric and reduced pressure plasmas, have been evaluated, with different degrees of success. Atmospheric pressure inductively coupled plasmas (ICPs), , capacitive plasmas, , and reduced pressure discharges such as low-pressure MIP 9,10 or low-pressure ICP 11 constitute representative examples of plasmas that have been investigated for nonmetal detection of gaseous organic compounds by OES 2-5,7-9 and MS. , …”
mentioning
confidence: 99%